Potential distribution of Rapistrum rugosum (turnip weed) - Michael, Pippa; Yeoh, P.; Scott, J. (Weeds Society of Victoria, 2012)
Rapistrum rugosum (L.) All. (Brassicaceae) is a widely distributed weed of annual crops, especially pulses, in southern Australia. With the south-west of Western Australia predicted to become drier and hotter due to climate change, the development of predictive models to determine future weed threats to the agricultural industry is essential for early intervention and to enable adaptation measures to be put in place. We measured the plant’s growth in relation to temperature and used this information along with soil moisture and phenology information based on the known distribution to derive growth parameters to develop a CLIMEX model. Under a warming climateR. rugosum is projected to increase its distribution in the northern hemisphere, but to decrease its distribution in Australia.